Landslides and sinkholes of the karst environment in the vicinity of the Ufa river - N. A. Orlova (Известия высших учебных заведений: Геология и разведка, 2022)
Introduction. As a result of the conducted route reconnaissance and geological engineering surveys, data about the development pattern of exogenous processes at a site adjoining the city of Ufa were obtained. This region is well studied due to the extensively developed karst. Although landslides are less prevalent here, their development is frequently connected with the karst intensification. Landslides, formed in sites of sinkholes and topographic lowering, are well represented in other regions of the Russian Federation. Aim. To study the characteristics of landslide formation. In addition, the mechanism of forming landslides, confined to rock massif decompaction zones, is analysed.Materials and methods. A mechanism of landslide formation in the sites of karst development is proposed. The work is based on the analysis of the results obtained in previous researchers of 1997, 2013 and 2017, interpretation of satellite images, digital terrain model and topographic, geomorphological and engineering-geological maps, as well as reconnaissance surveys. The peculiarity of engineering-geological conditions makes it possible to study the formation and development of two exogenous processes simultaneously (karst and landslides) in the selected area. The area under study included the exit section of Ufa city along the slopes of the Solotchi and Ufa rivers. According to the law established by Bondarik, Pendin and Yarg in 2007, “...some geological processes prepare others, which, in turn prepare the next ones, etc. and, as a result, so-called cascade processes develop...”. Exogenous geological processes of karst and landslides, developing in one section of the geological massif, are considered.Results. The formation of cavities is confined to the tectonic fracturing, along whose surface underground waters flow into the depths of the rock massif. The hydrodynamic zonation varies in time with the substraction of a filler and a release of previously formed cracks, cavities and voids. As long as the vertical pressure in soils and layer bearing capacity remain stable, no deformation of the massif above the cavity is observed. As a result of the study, the process sequence was presented for consideration, as well as the assumption was made about the lateral repulse crack deforming the slope surface after the formation of a block at the depth.Conclusion. The formation of karst sinkholes was demonstrated to intensify landslide processes on the slope surface.